Pengaruh Intellectual Capital dan Profitabilitas Terhadap Capital Gain pada Perusahaan Perbankan di Bursa Efek Indonesia Periode 2016 - 2020 - Ayu Rizki Yuliani; Lukita Tripermata; Aris Munandar (Journal of Accounting and Taxation, 2022)
This study aims to observe the significant effect of Intellectual Capital and Profitability on Capital Gain. This research was conducted on banking companies on the Indonesia Stock Exchange in the 2016-2020 period, which amounted to 12 companies as samples that met the criteria. The sampling technique used was purposive sampling technique. Collecting data using literature study and documentation. The data analysis method used is multiple linear regression analysis. The results of the research on the t test show that profitability has no and significant effect on the Capital Gain of banking companies listed on the IDX for the 2016-2020 period. Intellectual capital has a significant and significant effect on Capital Gain. banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The results of the research on the F test show that Intellectual Capital and Profitability have a simultaneous effect on Capital Gain.